A Brief 100 Year History of Carbon. (September 2017) - Kemp, Terence J.
Elemental carbon has been known from time immemorial in its forms of diamond and graphite, while the Industrial Revolution was powered by coal. The molecular structures of diamond and graphite were established following the inception of X-ray crystallography while the complex natures of charcoal and coal have been investigated for 100 years. Recent developments in activated charcoal are described in an article in this issue of Science Progress. However, no-one could have guessed that carbon would have presented such structural surprises as those of C60 fullerene, carbon nanotubes, and graphene. Materials science has benefited from the discovery of carbon fibres, and our understanding of the spectroscopy and bonding in the simplest carbon molecule, C2, has reached new depths.